Aerial photography of Russian Antarctic stations Mirny and Progress in summer of 2014/15 - S. S. Pryakhin; S. V. Popov; N. V. Sandalyuk; V. L. Mart'yanov; S. P. Polyakov (Лëд и снег)
Aerial photographing performed during the field season of 60th Russian Antarctic Expedition (2014/2015) made possible to construct a photoplan of the Mirny station. Its size is 3,5×3,5 km with resolution of 16 pixels/cm, and it will be used as a basis for designing of new airport. Similar work had been done over the Progress station along the route “Progress – Vostok”, about 35 km long. It was found that any crevasses dangerous for people and transport were absent on this area.